Evaluation of the accounting information system for sales of Suzuki cars at PT. Majestic Putra Sejahtera Makassar - Helmy, Latifa (Indonesia Accounting Research Journal, 2023)
Research on evaluating accounting information systems for car sales at PT. MegahPutra Sejahtera Makassar has implemented an accounting information system for car sales effectively and efficiently. The research was conducted using a qualitative descriptive analysis method. This method is carried out by collecting data by interviews and observations at PT. MegahPutra Prosperous Makassar. The results of the study concluded, that PT. MegahPutra Sejahtera Has implemented an accounting information system for car sales effectively and efficiently.